2019
DOI: 10.1186/s12863-019-0796-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of CfSnf1 in the development and pathogenicity of anthracnose fungus Colletotrichum fructicola on tea-oil tree

Abstract: BackgroundTea-oil tree (Camellia oleifera) is a unique edible-oil tree in China, and anthracnose occurs in wherever it is cultivated, causing great economic losses each year. We have previously identified the Ascomycete fungus Colletotrichum fructicola as the major pathogen of anthracnose in Ca. oleifera. The purpose of this study was to characterize the biological function of Snf1 protein, a key component of the AMPK (AMP-activated protein kinase) pathway, for the molecular pathogenic-mechanisms of C. fructic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…Targeted CfGCN5 gene deletion was carried out by the one-step replacement strategy as per our previous description ( Zhang et al, 2019 ). The two ∼1.0 kb sequences flanking CfGCN5 were overlapped to the two sides of the HPH (hygromycin resistance cassette) gene, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted CfGCN5 gene deletion was carried out by the one-step replacement strategy as per our previous description ( Zhang et al, 2019 ). The two ∼1.0 kb sequences flanking CfGCN5 were overlapped to the two sides of the HPH (hygromycin resistance cassette) gene, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that CfSnf1, a key component of AMPK (AMP-activated protein kinase), regulates the utilization of specific carbon sources, appressorium formation, and pathogenicity in C. fructicola ( Zhang et al, 2019 ). In Saccharomyces cerevisiae , ScSnf1 cooperates with the histone acetyltransferase ScGcn5 (general control non-derepressible 5) to regulate transcription ( Lo et al, 2001 ; Abate et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…oleifera anthracnose. We recently demonstrated that CfSnf1, CfSte50, and CfGcn5 were involved in pathogenicity by regulating the appressorium formation in C. fructicola ( Zhang et al, 2019 , 2021 ; Chen et al, 2020 ). Transcription factor of CfSte12 and the MAP Kinase CfPmk1 are key regulators of pathogenesis of C. fructicola ( Liang et al, 2019 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…fructicola were studied. Previously, we had shown that CfSNF1 , CfSTE50 , CfMFS1 and CfHAC1 were involved in regulating growth, stress response and pathogenicity (Chen et al, 2019, 2020; Yao et al, 2019; Zhang et al, 2019). Shang et al (2020) studied the effector molecule CfEC92 of C .…”
Section: Introductionmentioning
confidence: 99%
“…In this preliminary study, the functions of some genes of C. fructicola were studied. Previously, we had shown that CfSNF1, CfSTE50, CfMFS1 and CfHAC1 were involved in regulating growth, stress response and pathogenicity (Chen et al, 2019(Chen et al, , 2020Yao et al, 2019;Zhang et al, 2019). Shang et al (2020) studied the effector molecule CfEC92 of C. fructicola and found that the effector molecule inhibits the immune response of plants in the early stage of infection (Shang et al, 2020).…”
mentioning
confidence: 99%